2022
DOI: 10.1007/s10654-022-00841-0
|View full text |Cite
|
Sign up to set email alerts
|

Healthy lifestyle in older adults and life expectancy with and without heart failure

Abstract: Several lifestyle factors have been linked to risk for heart failure (HF) and premature mortality. The aim of this study was to estimate the impact of a healthy lifestyle on life expectancy with and without HF among men and women from a general population. This study was performed among 6113 participants (mean age 65.8 ± 9.7 years; 58.9% women) from the Rotterdam Study, a large prospective population-based cohort study. A continuous lifestyle score was created based on five lifestyle factors: smoking status, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Another study conducted in the U.S. indicated that adherence to 5 low-risk lifestyle factors could prolong life expectancy at age 50 years by 12.2 and 14.0 years for male and female adults, respectively [ 10 ]. More relevant, the Rotterdam Study, investigating the effects of lifestyle on life expectancy with and without heart failure, concluded that a healthy overall lifestyle was associated with a longer total life expectancy and years lived without heart failure [ 20 ]. Our findings were generally consistent with the above-mentioned studies, and we further provided more comprehensive evidence that a high CVH may improve not only total life expectancy but also life years without CVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted in the U.S. indicated that adherence to 5 low-risk lifestyle factors could prolong life expectancy at age 50 years by 12.2 and 14.0 years for male and female adults, respectively [ 10 ]. More relevant, the Rotterdam Study, investigating the effects of lifestyle on life expectancy with and without heart failure, concluded that a healthy overall lifestyle was associated with a longer total life expectancy and years lived without heart failure [ 20 ]. Our findings were generally consistent with the above-mentioned studies, and we further provided more comprehensive evidence that a high CVH may improve not only total life expectancy but also life years without CVD.…”
Section: Discussionmentioning
confidence: 99%
“…The MSLT was adopted to evaluate the associations of CVH status with the total life expectancy and the number of years that participants could expect to live with and without CVD, respectively. Detailed descriptions of MSLT have been presented previously [ 19 , 20 ]. In simple terms, the MSLT is a time-inhomogeneous, finite-space, continuous-time Markov model, which characterizes population movement over time in a finite, discrete and mutually exclusive state space as a Markov process.…”
Section: Methodsmentioning
confidence: 99%
“…An analysis of the factors involved in the life span highlights an involvement percentage of approximately 25% of the genetic influence, while the environment and the lifestyle exert 75%. As a result, lifestyle and eating habits are essential for life quality and longevity [51][52][53][54], simultaneously influenced by the emotional state (Figure 1). croplastics, pesticides, or heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the factors involved in the life span highlights an involvement percentage of approximately 25% of the genetic influence, while the environment and the lifestyle exert 75%. As a result, lifestyle and eating habits are essential for life quality and longevity [51][52][53][54], simultaneously influenced by the emotional state (Figure 1). According to the data published in 2020 related to Romania s health profile, life expectancy, which increased after 2000, was seriously affected by the COVID-19 pandemic, falling far below the European Union (EU) average.…”
Section: Introductionmentioning
confidence: 99%
“…Its application, which is closely linked to innovation, is currently being carried out in very diverse contexts, such as education (Behl et al, 2022; Murillo-Zamorano et al, 2020), human resources (Murawski, 2021), tourism (Shi et al, 2022) and e-government (Contreras-Espinosa & Blanco-M, 2022). In the health field, gamification can be an effective tool to make people more committed to and responsible in their decisions such as, for example, the case of the patient adhering more easily and continuously over time to the treatments prescribed by the medical practitioner, as well as to promote the acquisition of new health behaviors and habits (Uechi et al, 2018), which is essential to increasing life expectancy (Limpens et al, 2022; Sun et al, 2021). In this sense, gamification has been used to promote physical activity (Koivisto & Hamari, 2019), to improve nutrition (Kurtzman et al, 2018), to promote adherence to medication (Abdul Rahim & Thomas, 2017), and to encourage hand hygiene (Lapao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%